The Business Cycle and the Financial Cycle: Granger Causality for the Peruvian Economy, 2000 – 2019 - Crispín , Ángel Renato Meneses; Silva, Mg. Omar Cosme; Villarrue, Mg. Miguel Ángel Leon; Pérez, Mg. William Moises Cruzado (Journal of Ecohumanism, 2024)
It is relevant to know the relationship between the financial and business cycles to prevent the appearance of financial crises and their negative effects on the macroeconomy. In this sense, a better understanding of the links between financial cycles and the business cycle of Peru can provide valuable information for economic and macroprudential policy decisions. This study examines the causal relationship between Peru’s financial and business cycles. The dynamic factors methodology is used to measure the financial cycle, taking four representative indicators of the financial sector: Volume of loans to the private sector (credit market), the Lima Stock Exchange General Index (stock market), Embig Peru (bond market), and the Exchange Rate (currency market) (Ramos, 2019). On the one hand, using the Granger causality test in the frequency domain, it was found that the financial cycle causes the business cycle at frequencies greater than 10 quarters (2.5 years). In contrast, the business cycle does not cause the financial cycle.